Applications of Green Synthesized Silver Nanoparticles Using Calotropis Gigantea - Bhawna Nohwal; Nitish Kumar; Reeti Chaudhary (International Journal of Pharma and Bio Sciences, 2021)
Nanoparticles have gained utmost significance due to their unique physical and chemical properties such as higher surface area, lower melting point, specific magnetic property, mechanical strength and specific optical properties. The green biological synthesis method used in the present study is a non-toxic alternative to the conventional physical and chemical nanoparticles synthesis and could be suitable for large scale production biologically. This method could be appropriate for various prospective treatments. The unique antimicrobial properties of silver (Ag) nanoparticles gained high attention in the field of nanotechnology. Calotropis gigantea has wide medicinal applications, hence it is utilized for Ag nanoparticles synthesis. In the present study, synthesis of silver nanoparticles is reported by bioreduction of Calotropis gigantea extract using silver nitrate at room temperature. The synthesized nanoparticles were then characterized and evaluated for antimicrobial and antioxidant activity. Silver nanoparticles were characterized in terms of synthesis, size distribution and microscopic evaluation by UV-Visible spectroscopy and Transmission Electron Microscope (TEM). The change of color from light brown to dark brown confirmed the biosynthesis of silver nanoparticles. Nearly spherical nanoparticles with a majority of particle size less than 50 nm were confirmed. X-ray diffraction (XRD) pattern confirmed the existence of silver in the sample. The XRD diffraction patterns revealed four diffraction peaks at 38.45°, 44.83°, 64.7° and 78.06° indexed to 110, 111, 211, 222 planes fcc. In vitro dose dependent free radical scavenging activity of biosynthesized silver nanoparticles was analyzed using 1, 1-Diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis [3-ethylbenzothiazoline-6-sulphonic acid] salt (ABTS). The synthesized nanoparticles have the tendency to prevent cell/tissue damage occurring because of the oxidative stress. The antibacterial activity was performed against B. subtilis, S. aureus, E. coli and S. typhi. These nanoparticles revealed higher antibacterial activity against S. typhi and E. coli as compared to S. aureus and B. subtilis. The minimum inhibitory concentrations were in the range 6.6 nM and 13.2 nM.